2014
DOI: 10.1051/0004-6361/201424146
|View full text |Cite
|
Sign up to set email alerts
|

GW Orionis: Inner disk readjustments in a triple system

Abstract: Context. Disks are expected to dissipate quickly in binary or multiple systems. Investigating such systems can improve our knowledge of the disk dispersal. The triple system GW Ori, still harboring a massive disk, is an excellent target. Aims. We study the young stellar system GW Ori, concentrating on its accretion, wind activity and disk properties. Methods. We use high-resolution optical spectra of GW Ori to do spectral classification and derive the radial velocities (RV). We analyze the wind and accretion a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 144 publications
2
30
1
Order By: Relevance
“…The residuals from our initial fit indicated that our formal velocity uncertainties are underestimated, and so the uncertainties on each measurement are scaled to achieve a reduced χ 2 ν = 1 for our final solution. The period of the inner orbit is consistent with that of Mathieu et al (1991) and Fang et al (2014); however, due to the SB2 nature of the system, most other orbital parameters are significantly different. We find a larger semi-amplitude for the primary, K A = 8.36 ± 0.14 km s −1 , a mass ratio of q ≡ M B /M A = 0.60 ± 0.02, and a statistically significant eccentricity e in = 0.13 ± 0.02.…”
Section: An Updated Model Of the Stellar Orbitssupporting
confidence: 53%
See 1 more Smart Citation
“…The residuals from our initial fit indicated that our formal velocity uncertainties are underestimated, and so the uncertainties on each measurement are scaled to achieve a reduced χ 2 ν = 1 for our final solution. The period of the inner orbit is consistent with that of Mathieu et al (1991) and Fang et al (2014); however, due to the SB2 nature of the system, most other orbital parameters are significantly different. We find a larger semi-amplitude for the primary, K A = 8.36 ± 0.14 km s −1 , a mass ratio of q ≡ M B /M A = 0.60 ± 0.02, and a statistically significant eccentricity e in = 0.13 ± 0.02.…”
Section: An Updated Model Of the Stellar Orbitssupporting
confidence: 53%
“…However, they found the disk has an intermediate inclination to the line of sight (i disk ≈ 35 • ), in apparent conflict with the eclipse model. Indeed, this adds to a collection of indirect evidence for a more complicated geometry in the inner disk, including mid-infrared fluxes that vary on ∼year timescales (Fang et al 2014), and CO rovi-brational emission lines with multi-component profiles (which requires a complicated geometry and/or temperature structure in the inner disk; Najita et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this depends on the ability of the planet to block the gas flow (and not only dust) through the gap, which is uncertain (Müller & Kley 2013;Zhu & Stone 2014) and inconsistent with some of the accreting binary systems known to date (e.g. Fang et al 2014), including cases such as 82-272 in Tr 37, which is an accreting spectroscopic binary (Sicilia-Aguilar et al 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…Such replenishing can be occasionally enhanced by a collision between the largest parental bodies or by gravitational stirring from a nearby planet (Krivov 2010). Small amounts of dust from the outer disk passing through the planet-induced gap region (Pinilla et al 2016) can also be an unsteady supply of inner NIR-emitting dust and cause NIR variations on timescale of several decades (e.g., in the case of GW Ori, Fang et al 2014). …”
Section: Nir Variability Of the Inner Diskmentioning
confidence: 99%